Commentary-practicing state of the art occlusion in the Digital Era of Dentistry - Kerstein RB (International Journal of Oral and Craniofacial Science - Peertechz Publications, 2022)
New technological developments in modern dental medicine offer clinicians insight and treatment advances to many outdated, dogmatic concepts that have been widely believed for many years, despite there being a lack of scientific evidence to support them. This is especially true in the field of Dental Occlusion, whose scientific development has been hampered by the use of traditional, non-digital occlusal indicators that do not quantify occlusion, other than possibly describing "contact area".